Transforming Healthcare with Nanomedicine: A SWOT Analysis of Drug Delivery Innovation - Zhang H; Li S; Ma X (Drug Design, Development and Therapy, 2024)
Hao Zhang,1 Suping Li,1 Xingming Ma2 1Department of Nuclear Medicine, Affiliated Hospital of North Sichuan Medical College North Sichuan Medical College, Nanchong, 637000, People’s Republic of China; 2School of Health Management, Xihua University, Chengdu, 610039, People’s Republic of ChinaCorrespondence: Hao Zhang, Department of Nuclear Medicine, Affiliated Hospital of North Sichuan Medical College, North Sichuan Medical College, Nanchong, 637000, People’s Republic of China, Tel +86-0817-2242705, Email zhanghao_112_sh@126.comObjective: Nanomedicine represents a transformative approach in biomedical applications. This study aims to delineate the application of nanomedicine in the biomedical field through the strengths, weaknesses, opportunities, and threats (SWOT) analysis to evaluate its efficacy and potential in clinical applications.Methods: The SWOT analysis framework was employed to systematically review and assess the internal strengths and weaknesses, along with external opportunities and threats of nanomedicine. This method provides a balanced consideration of the potential benefits and challenges.Results: Findings from the SWOT analysis indicate that nanomedicine presents significant potential in drug delivery, diagnostic imaging, and tissue engineering. Nonetheless, it faces substantial hurdles such as safety issues, environmental concerns, and high development costs. Critical areas for development were identified, particularly concerning its therapeutic potential and the uncertainties surrounding long-term effects.Conclusion: Nanomedicine holds substantial promise in driving medical innovation. However, successful clinical translation requires addressing safety, cost, and regulatory challenges. Interdisciplinary collaboration and comprehensive strategic planning are crucial for the safe and effective application of nanomedicine.Keywords: nanomedicine, drug delivery systems, SWOT analysis, biomedical application, safety, interdisciplinary collaboration